Prediction of groundwater level in slope areas by using resistivity method / Siti Norizan Mohd Ali ... [et al.] - Mohd Ali, Siti Norizan; Awang, Haryati; Osman, Nur Masyitah; Md Hassan, Ahmad Syauqi (2012)
@owadays, so many methods of in-situ testing such as piezometercan be applied to explore and investigate the presence of water in the ground especially in the hilly areas. The groundwater table is one of the main important factors in slope stability design. Therefore, a research has been conducted and a two-dimensional electrical resistivity imaging was carried out to predict the groundwater table at slope areas. These techniques can be used to image the slopes, measure and make predictions on the groundwater table. The groundwater table of the slopes is generally low, causing the soils to be mostly unsaturated except immediately after a rainfall. Generally, the rain water that infiltrates into the ground will increase the groundwater table and hence trigger slope failures. In the conventional method; a piezometer is normally used to monitor the groundwater level. However, the results that came from the piezometer are still not enough to be as a reference to predict the rise of groundwater table at the slope areas. As an extra precaution any measures, the two-dimensional electrical resistivity imaging method have been used to assist the monitoring works on slopes to get additional information and assist in the design of slope stability